Accounting for depreciation: the valuation and matching approaches: concepts and application / Ahmad Hamdan - Hamdan, Ahmad (2023)
Depreciation of fixed assets is an integrated part of the accounting system. In fact, it is required by the Standards, in particular the International Accounting Standards No. 4 (IAS 4) and also the Statement of Standard Accounting Practice No. 12 (SSAP 12) , that fixed assets should be depreciated over the period of their useful life on a systematic basis. Depreciation can have a significant effect in determining and presenting the financial position and results of operations of enterprises.